An iterative solution for the travelling salesman problem. (13th February 2006) - Su, L.J.; Nie, Y.Y.
The travelling salesman problem (TSP) is a typical NP-hard problem. In this paper, a well implied enumeration method for TSP is presented where the solution of the TSP is obtained by an iterative process. At each iteration, an integer linear programming is solved by the isometric surface method. The efficiency of the algorithm is dependent on that of the integer linear programming.